“How much do I have to pay for my dream?” : Considerations on the realities of and problems encountered by Korean elite sports as were depicted in the movie 〈Not Out〉 - Sang Jin Yoon (Cheyuk gwahag yeon-gu, 2023)
PURPOSE This study aimed to examine contemporary sports reality and its problems through the feature-length independent film <Not Out>, which focused on baseball, a popular sport, and highlighted its rather dark side. METHODS The researcher performed a textual analysis using the perspective of critical theory. RESULTS Gwang-ho was the hero of a walk-off hit in the national baseball competition final, who suffered from three career strikes during his third year of high school and thought that he had bright future ahead of him. Before the amateur draft, Gwang-ho boldly rejected the proposal of a trainee contract from a professional team (strike 1), then he was subsequently not selected in the amateur draft (strike 2), before he applied for the college entrance examination for baseball specialties, and was eventually rejected. (strike 3) In the end, he was able to enter college through a bribe given by his father (not-out situation). CONCLUSIONS <Not Out> is a film based on a true story, and it showcased the realities of elite sports by revealing the dynamics of society and school, where the main character responded with reluctance and indifference. This movie highlighted the realities of delinquency, violence, abusive language, bribe, and violations of the right to learn and how these have continued to evade the law despite being thought to be gone.